A new species of Epidendrum (Laeliinae: Orchidaceae) from the province of Zamora Chinchipe in Ecuador - Lapo-Gonzalez, Nadia; Hágsater, Eric; Vélez-Abarca, Leisberth; Uyaguari, Johny J. Mendoza; Jiménez, Marco M.; Kuethe, J.r. (Phytotaxa, 2024)
A new species of Epidendrum from the province of Zamora Chinchipe, belonging to the Incomptum informal group, is described and illustrated. Information on its distribution, habitat, phenology, and conservation status is provided. The new species, Epidendrum quimiense, is compared with Epidendrum marci-jimeneziorum, Epidendrum chisquillense and Epidendrum ulcumanoae from which it is easily distinguished by having green to yellowish-green flowers, the ovary ventrally inflated along the apical half and the lip bilobed, reniform with the sides strongly revolute and apron-shaped.